Motivation and motivational climate among elite hammer throwers - Benczenleitner Ottó; Bognár József; Révész László; Paksi Judit; Csáki István; Géczi Gábor (Sciendo, 2013)
Study aim: The purpose of the study was to explore the characteristics of the motivational factors and the motivational climate of elite hammer throwers in the most prestigious and most successful club in Hungary.